(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This study examined psycho-emotional and cognitive disorders in women of reproductive age with hypothyroidism and evaluated the effectiveness of cognitive-behavioral therapy (CBT). A total of 90 women with confirmed hypothyroidism (mean age 34.8 ± 8.7 years) and 40 healthy women as a control group were included. Psycho-emotional state was assessed using PHQ-9. At baseline, moderate depression was found in 57.8%, mild in 31.1%, and severe in 11.1% of hypothyroid patients (p<0.05). After a CBT course, significant reductions in depression (p<0.01) were observed. CBT is an effective psychocorrectional approach to improving mental health and quality of life in women with hypothyroidism.